A battery cell and a lithium battery using the same

By inserting non-adhesive polymers into the separator of the lithium-ion battery and performing pressing treatment, the problem of insufficient bonding performance between the separator and the electrode sheet is solved, and the battery electrical and safety performance is improved.

CN118487003BActive Publication Date: 2025-02-07HUIZHOU EVE POWER CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410622519.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-02-07
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

The bonding performance between the existing lithium-ion battery separator and the electrode sheet is insufficient, resulting in the wrinkle of the electrode sheet and the internal resistance increase, affecting the electrical and safety performance of the battery.

Method used

The composite cell structure is adopted, wherein the separator comprises a porous substrate layer and a porous active layer. By inserting a non-binding polymer in the porous active layer on the positive electrode and the negative electrode side, and performing a pressing treatment under specific temperature and pressure conditions. Achieving a close fit between the diaphragm and the pole sheet.

Benefits of technology

The bonding effect between the composite diaphragm and the electrode sheet is improved, the structural stability and cyclic stability of the battery cell are enhanced, and the electrical and safety performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004848109560000101
    Figure BDA0004848109560000101
  • Figure BDA0004848109560000111
    Figure BDA0004848109560000111
Patent Text Reader

Abstract

The present invention provides a battery cell, comprising a positive electrode sheet, a composite separator and a negative electrode sheet arranged in sequence, wherein the composite of the positive electrode sheet and the composite separator is achieved by a pressing process I, wherein the pressing temperature T1 of the pressing process I satisfies 50°C≤T1<Tg value of non-binder polymer C1, and the pressing pressure is not less than 0.2 tons; the composite of the negative electrode sheet and the composite separator is achieved by a pressing process II, wherein the pressing temperature T2 of the pressing process II satisfies 28°C≤T2<Tg value of non-binder polymer C2, and the pressing pressure is not less than 0.2 tons. The battery cell provided by the present invention regulates the compaction density of the first positive and negative electrode active coatings in the direction of the composite separator, and on this basis, further specifically limits the composite conditions of the composite separator and the positive and negative electrode sheets, thereby enabling the composite separator to maintain a stable and firm composite with the positive and negative electrode sheets, thereby improving the structural stability and cycle stability of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to a battery cell and a lithium battery using the same. Background Art

[0002] As a key material of lithium-ion batteries, the main function of the diaphragm is to separate the positive and negative electrodes to prevent them from contacting and short-circuiting. At the same time, the diaphragm has a microporous structure that can provide a channel for the movement of lithium ions. The material of the diaphragm is generally polyethylene (PE) or polypropylene (PP). The PE and PP diaphragms are not tightly fitted to the pole pieces, which can easily cause the pole pieces to wrinkle and increase the internal resistance, which in turn causes a series of electrical performance and safety performance problems of the battery.

[0003] Therefore, how to improve the bonding performance between the diaphragm and the electrode sheets so as to maintain a high degree of fit between the diaphragm and the positive and negative electrode sheets is a technical problem that technicians in this field urgently need to solve in their research. Summary of the invention

[0004] The purpose of the present invention is to provide a composite battery cell and a lithium battery using the same, wherein the separator in the composite battery cell can maintain a high degree of fit with the positive and negative electrode sheets, so that the composite battery cell has both excellent electrical performance and safety performance.

[0005] According to one aspect of the present invention, a battery cell is provided, comprising a positive electrode sheet, a composite separator and a negative electrode sheet arranged in sequence; the positive electrode sheet comprises a positive electrode collector and a first positive electrode active coating, the first positive electrode active coating being arranged on the surface of the positive electrode collector facing the composite separator; the negative electrode sheet comprises a negative electrode collector and a first negative electrode active coating, the first negative electrode active coating being arranged on the surface of the negative electrode collector facing the composite separator; the composite separator comprises a porous substrate layer, a positive electrode side porous active layer, and a negative electrode side porous active layer, the surface of the porous substrate layer facing the positive electrode sheet is the first surface, the positive electrode side porous active layer is arranged on the first surface, the surface of the porous substrate layer facing the negative electrode sheet is the second surface, and the negative electrode side porous active layer is arranged on the second surface; the positive electrode side porous active layer comprises a first base coating and a non-binder polymer C1 embedded in the first base coating, and D of the non-binder polymer C1 50 > the thickness of the first base coating; the porous active layer on the negative electrode side includes a second base coating and a non-binder polymer C2 embedded in the second base coating, and the D of the non-binder polymer C2 50 >Thickness of the second base coating; compaction density of the first positive electrode active coating is 2.05-3.60 g / cm 3 ; The compaction density of the first negative electrode active coating is 1.40 to 1.85 g / cm 3The composite of the positive electrode sheet and the composite separator is achieved by pressing treatment I, the pressing temperature T1 of pressing treatment I satisfies 50°C ≤ T1 < Tg value of non-binder polymer C1, and the pressing pressure of pressing treatment I is not less than 0.2 tons; the composite of the negative electrode sheet and the composite separator is achieved by pressing treatment II, the pressing temperature T2 of pressing treatment II satisfies 28°C ≤ T2 < Tg value of non-binder polymer C2, and the pressing pressure of pressing treatment II is not less than 0.2 tons. The compaction density of the first positive active coating can be 2.05g / cm 3 , 2.2g / cm 3 , 2.35g / cm 3 , 2.5g / cm 3 , 2.65g / cm 3 , 2.7g / cm 3 , 2.85g / cm 3 、3.0g / cm 3 、3.15g / cm 3 3.30g / cm 3 、3.45g / cm 3 、3.60g / cm 3 The compaction density of the first negative electrode active coating layer can be 1.40 g / cm 3 , 1.50g / cm 3 , 1.60g / cm 3 , 1.70g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. In the composite battery cell provided by the present invention, a first positive electrode active coating with a specific compaction density is provided on the positive electrode sheet, and the surface of the positive electrode sheet is relatively smooth and has fewer pores. Based on this, by setting the non-binder polymer C1, a distinct convex structure is formed on the surface of the porous active layer on the positive electrode side of the composite separator, and the composite separator is composited with the positive electrode sheet under the condition of high temperature pressing treatment I. Thus, the convex structure formed by the non-binder polymer C1 can be fully and effectively filled in the smaller pores on the surface of the positive electrode sheet, thereby achieving a close fit between the composite separator and the positive electrode sheet; at the same time, due to the T of the non-binder polymer C1 The high g value and excellent mechanical properties are conducive to the composite diaphragm having sufficient structural stability and thermal stability; the negative electrode sheet is provided with a first negative electrode active coating with a specific compaction density. The surface of the negative electrode sheet is relatively rough and has many pores. Based on this, the non-binder polymer C2 is set to form an obvious convex structure on the surface of the porous active layer on the negative electrode side of the composite diaphragm, and the composite diaphragm is compounded with the negative electrode sheet under the condition of a relatively low temperature pressing treatment II. As a result, the convex structure formed by the non-binder polymer C2 is easily inserted into the larger pores on the surface of the negative electrode sheet, thereby achieving a close fit between the composite diaphragm and the positive electrode sheet.

[0006] In summary, the battery cell provided by the present invention regulates the compaction density of the first positive and negative electrode active coatings toward the composite diaphragm, and on this basis, further specifically limits the composite conditions of the composite diaphragm and the positive and negative electrode sheets. As a result, the composite diaphragm and the positive and negative electrode sheets can be stably and firmly composited, thereby effectively improving the bonding effect between the composite diaphragm and the positive and negative electrode sheets, and improving the structural stability and cycle stability of the battery cell.

[0007] Preferably, the non-adhesive polymer C1 is selected from one or more of polymethyl acrylate, polyethyl acrylate, polybutyl acrylate, polymethyl methacrylate, butyl acrylate-styrene copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer and ethylene-methyl methacrylate copolymer.

[0008] Preferably, the non-adhesive polymer C2 is selected from one or more of polymethyl acrylate, polyethyl acrylate, polybutyl acrylate, polymethyl methacrylate, butyl acrylate-styrene copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer and ethylene-methyl methacrylate copolymer.

[0009] Preferably, D of the non-adhesive polymer C1 50 :Thickness of the first base coating layer = (1.3-4): 1. D of the non-adhesive polymer C150 : The thickness of the first base coating layer can be 1.3:1, 2:1, 2.7:1, 3.4:1 μm, 4:1, etc., but is not limited to the listed values. Other values ​​not listed in the numerical range are also applicable. By properly setting the D of the non-adhesive polymer C1 50 The ratio of the thickness of the non-adhesive polymer C1 to the thickness of the first base coating is beneficial to ensure that the non-adhesive polymer C1 can be stably and firmly embedded in the first base coating of the composite diaphragm, thereby further helping the protruding structure formed by the non-adhesive polymer C1 to be stably and firmly embedded in the pores of the positive electrode sheet, thereby effectively improving the bonding effect between the composite diaphragm and the positive electrode sheet.

[0010] Preferably, the thickness of the first base coating is 1 to 4 μm, and the D 50 The thickness of the first positive electrode active coating layer is 3 to 7 μm, and the thickness of the first positive electrode active coating layer is 40 to 150 μm.

[0011] Preferably, D of the non-adhesive polymer C2 is 50 :Thickness of the second base coating = (1.3-4): 1. D of the non-adhesive polymer C2 50 : The thickness of the second base coating can be 1.3:1, 2:1, 2.7:1, 3.4:1, 4:1, etc., but is not limited to the listed values. Other values ​​not listed in the numerical range are also applicable. By properly setting the D of the non-adhesive polymer C2 50 The ratio of the thickness of the non-adhesive polymer C2 to the thickness of the second base coating is beneficial to ensure that the non-adhesive polymer C2 can be stably and firmly embedded in the second base coating of the composite diaphragm, thereby further helping the protruding structure formed by the non-adhesive polymer C2 to be stably and firmly embedded in the pores of the negative electrode sheet, thereby effectively improving the bonding effect between the composite diaphragm and the negative electrode sheet.

[0012] Preferably, the thickness of the second base coating is 1 to 4 μm, and the D 50 The thickness of the first negative electrode active coating layer is 3 to 7 μm, and the thickness of the first negative electrode active coating layer is 40 to 100 μm.

[0013] Preferably, the mass proportion (weight proportion) of the non-adhesive polymer C1 in the porous active layer on the positive electrode side is 3% to 22%. The mass proportion of the non-adhesive polymer C1 in the porous active layer on the positive electrode side can be 3%, 7%, 11%, 15%, 19%, 22%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Since the porosity of the above-mentioned positive electrode sheet is relatively low, the content of the non-adhesive polymer C1 in the porous active layer on the positive electrode side is effectively regulated so that the surface of the composite diaphragm has a sufficient amount of protrusion structure, which effectively increases the probability of the non-adhesive polymer C1 being embedded in the first positive active coating of the positive electrode sheet, thereby improving the fit between the composite diaphragm and the positive electrode sheet; at the same time, the high Tg value non-adhesive polymer C1 of the above content can effectively ensure the thermal shrinkage performance and air permeability of the diaphragm, so that the battery has excellent electrical performance and safety performance.

[0014] Preferably, the mass proportion (weight proportion) of the non-binder polymer C1 in the positive electrode side porous active layer is 17% to 22%.

[0015] Preferably, the mass proportion (weight proportion) of the non-binder polymer C2 in the porous active layer on the negative electrode side is 2% to 17%. The mass proportion of the non-binder polymer C2 in the porous active layer on the negative electrode side can be 2%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Since the Tg value of the non-binder polymer C2 is relatively low, more non-binder polymer C2 is likely to cause the thermal shrinkage rate of the composite diaphragm to increase and the thermal stability to decrease. Therefore, by further effectively regulating the content of the non-binder polymer C2 in the porous active layer on the negative electrode side, the appropriate content of the low Tg value non-binder polymer C2 can not only ensure the excellent thermal shrinkage performance of the composite diaphragm, but also ensure that the surface of the composite diaphragm has an appropriate amount of convex structure, so that the fit between the composite diaphragm and the negative electrode sheet is maintained at a high level.

[0016] Preferably, the mass proportion (weight proportion) of the non-binder polymer C2 in the porous active layer on the negative electrode side is 7% to 12%.

[0017] Preferably, the Tg value of the non-binder polymer C1 is 55 to 90°C. The Tg value of the non-binder polymer C1 can be 55°C, 65°C, 75°C, 85°C, 90°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The non-binder polymer C1 within the above Tg value range has good mechanical properties, and has sufficient elasticity to be fully inserted into the pores of the positive electrode sheet during the composite process of the composite separator and the positive electrode sheet, thereby improving the fit between the composite separator and the positive electrode sheet, and has high mechanical strength, which can improve the thermal stability of the composite separator and the cycle stability of the battery.

[0018] Preferably, the Tg value of the non-binder polymer C2 is 30 to 90°C. The Tg value of the non-binder polymer C2 may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The non-binder polymer C2 within the above Tg value range is easy to be stably and firmly embedded in the pores of the negative electrode sheet during the composite process of the composite separator and the negative electrode sheet, thereby improving the fit between the composite separator and the negative electrode sheet.

[0019] Preferably, the Tg value of the non-binder polymer C2 is 30-53°C.

[0020] Preferably, the pressing temperature T1 of pressing process I is 50-70°C, and the pressing pressure of pressing process I is 0.2-14 tons (t); the pressing temperature T2 of pressing process II is 28-48°C, and the pressing pressure of pressing process II is 0.2-14 tons (t). The pressing temperature T1 of pressing process I can be 50°C, 60°C, 70°C, etc., and the pressing pressure of pressing process I can be 0.2 tons, 1 ton, 3 tons, 5 tons, 7 tons, 9 tons, 11 tons, 13 tons, 14 tons, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. The pressing temperature T2 of pressing treatment II can be 28°C, 38°C, 48°C, etc., and the pressing pressure of pressing treatment II can be 0.2 tons, 1 ton, 3 tons, 5 tons, 7 tons, 9 tons, 11 tons, 13 tons, 14 tons, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the first positive electrode active coating layer comprises a first positive electrode active material, and the D 50 The first negative electrode active coating comprises a first negative electrode active material, and the D 50 5~20μm.

[0022] Preferably, the first positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, ternary material, lithium cobalt oxide, and lithium manganese oxide.

[0023] Preferably, the first negative electrode active material includes at least one of graphite, hard carbon, soft carbon, and silicon-based materials.

[0024] According to another aspect of the present invention, a lithium battery is provided, comprising the above-mentioned battery cell. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0026] Example 1

[0027] This embodiment provides a lithium battery, and the preparation method thereof comprises the following steps:

[0028] 1. Preparation of positive electrode sheet:

[0029] The first positive electrode active material (particle size D 50 The positive electrode slurry is coated on an aluminum foil and dried at 85°C in a vacuum environment for 24 hours to obtain a positive electrode sheet.

[0030] The positive electrode sheet includes a positive electrode current collector and a first positive electrode active coating, wherein the compaction density of the first positive electrode active coating is 2.45 g / cm 3 .

[0031] 2. Preparation of negative electrode sheet:

[0032] The first negative electrode active material (particle size D 50 Graphite with a diameter of 12.5 μm), conductive carbon black (SP), and sodium carboxymethyl cellulose (CMC) as a binder are uniformly mixed in a mass ratio of 92:4:4, dispersed in deionized water to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil and dried at 100° C. in a vacuum environment for 12 h to obtain a negative electrode sheet.

[0033] The negative electrode sheet includes a negative electrode current collector and a first negative electrode active coating, and the compaction density of the first negative electrode active coating is 1.50 g / cm 3 .

[0034] 3. Preparation of diaphragm:

[0035] S1, adding a polyethylene (PE) porous substrate into a material tank, and preparing a porous substrate layer by extrusion, sheet casting, longitudinal stretching, extraction and heat setting;

[0036] S2, adding inorganic particle A aluminum oxide, binder polymer B polyvinylidene fluoride, and non-binder polymer C1 butyl acrylate-styrene copolymer into a stirring tank at a mass ratio of 76:4:20, adding a solvent and stirring and dispersing them uniformly, and then continuously dispersing them at a stirring speed of 1000 rpm for 100 minutes to form a first coating slurry;

[0037] The inorganic particles A aluminum oxide, the binder polymer B polyvinylidene fluoride, and the non-binder polymer C2 butyl acrylate-styrene copolymer are added into a stirring tank at a mass ratio of 86:4:10, and a solvent is added to stir and disperse them uniformly, and then the stirring speed is continued at 1000 rpm for 100 minutes to form a second coating slurry;

[0038] S3, applying the first coating slurry to the first surface of the porous substrate layer (the surface of the porous substrate layer facing the positive electrode sheet is the first surface) to form a porous active layer on the positive electrode side; the porous active layer on the positive electrode side includes a first base coating and a non-binder polymer C1 embedded in the first base coating, wherein the thickness of the first base coating is 2.0 μm, and the particle size D of the non-binder polymer C1 is 50 The non-binder polymer C1 has a mass ratio of 20% in the porous active layer on the positive electrode side, and a Tg value of 60°C (the non-binder polymer C1 is composed of butyl acrylate-styrene copolymer, and the butyl acrylate-styrene copolymer is prepared by a molar ratio of butyl acrylate to styrene of 2.6:7.4).

[0039] S4, coating the second coating slurry on the second surface of the porous substrate layer (the surface of the porous substrate layer facing the negative electrode sheet is the second surface) to form a porous active layer on the negative electrode side; the porous active layer on the negative electrode side includes a second base coating and a non-binder polymer C2 embedded in the second base coating, wherein the thickness of the second base coating is 2.0 μm, and the particle size D of the non-binder polymer C2 is 50 The non-binder polymer C2 has a mass ratio of 10% in the porous active layer on the negative electrode side, and a Tg value of 40°C (the non-binder polymer C2 is composed of butyl acrylate-styrene copolymer, and the butyl acrylate-styrene copolymer is prepared by a molar ratio of butyl acrylate to styrene of 3.8:6.2).

[0040] S4. After coating, the composite membrane is dried in an oven to obtain the composite membrane.

[0041] 4. Preparation of electrolyte:

[0042] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0043] 5. Preparation of battery cells:

[0044] (1) Composite diaphragm and positive electrode sheet: pressing treatment I (pressing temperature T1 is 52°C, pressing pressure is 1.2t, pressing time is 3s);

[0045] (2) Composite diaphragm and negative electrode sheet: pressing treatment II (pressing temperature T1 is 30°C, pressing pressure is 0.8t, pressing time is 1s);

[0046] (3) Prepare bare battery cells.

[0047] 6. Assemble lithium battery

[0048] The bare battery cell is placed in an outer packaging shell, and after drying, the above electrolyte is injected, and the lithium battery is prepared through vacuum packaging, standing, forming, and constant capacity processes.

[0049] Example 2

[0050] This embodiment is used to prepare a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the D 50 Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0051] Example 3

[0052] This embodiment is used to prepare a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the D 50 Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0053] Example 4

[0054] This embodiment is used to prepare a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the D 50 Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0055] Example 5

[0056] This embodiment is used to prepare a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the D 50 Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0057] Example 6

[0058] This example prepares a lithium battery with reference to Example 1. The difference between this example and Example 1 is that in the process of compounding the separator in this example, the mass proportion of the non-binder polymer C1 in the porous active layer on the positive electrode side is 2%. Except for the above difference, the materials and process operations used in this example are strictly consistent with those in Example 1.

[0059] Example 7

[0060] This example prepares a lithium battery with reference to Example 1. The difference between this example and Example 1 is that in the process of compounding the separator in this example, the mass proportion of the non-binder polymer C1 in the porous active layer on the positive electrode side is 25%. Except for the above difference, the materials and process operations used in this example are strictly consistent with those in Example 1.

[0061] Example 8

[0062] This embodiment prepares a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the process of compounding the separator in this embodiment, the mass proportion of the non-binder polymer C2 in the porous active layer on the negative electrode side is 1%. Except for the above difference, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0063] Example 9

[0064] This example prepares a lithium battery with reference to Example 1. The difference between this example and Example 1 is that in the process of compounding the separator in this example, the mass proportion of the non-binder polymer C2 in the porous active layer on the negative electrode side is 18%. Except for the above difference, the materials and process operations used in this example are strictly consistent with those in Example 1.

[0065] Example 10

[0066] This embodiment prepares a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the Tg value of the non-binder polymer C1 used in this embodiment is 98°C (the non-binder polymer C1 is composed of polymethyl methacrylate and butyl acrylate-styrene copolymer, wherein the molar ratio of polymethyl methacrylate and butyl acrylate-styrene copolymer is 8.4:1.6, and the butyl acrylate-styrene copolymer is prepared by butyl acrylate and styrene in a molar ratio of 2.6:7.4). Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0067] Embodiment 11

[0068] This embodiment prepares a lithium battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the Tg value of the non-binder polymer C2 used in this embodiment is 98°C (the non-binder polymer C2 is composed of polymethyl methacrylate and butyl acrylate-styrene copolymer, wherein the molar ratio of polymethyl methacrylate and butyl acrylate-styrene copolymer is 8.4:1.6, and the butyl acrylate-styrene copolymer is prepared by butyl acrylate and styrene in a molar ratio of 2.6:7.4). Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0069] Example 12

[0070] This embodiment refers to Example 1 to prepare a lithium battery. The difference between this embodiment and Example 1 is that in the process of combining the composite separator and the positive electrode sheet in this embodiment, the pressing temperature is 50° C. and the pressing pressure is 0.2 tons. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0071] Embodiment 13

[0072] This example prepares a lithium battery with reference to Example 1. The difference between this example and Example 1 is that in the process of compounding the composite separator and the negative electrode sheet in this example, the pressing temperature is 28° C. and the pressing pressure is 0.2 tons. In addition to the above differences, the materials and process operations used in this example are strictly consistent with those in Example 1.

[0073] Comparative Example 1

[0074] This comparative example prepares a lithium battery with reference to Example 1. The difference between this comparative example and Example 1 is that in the process of compounding the composite separator and the positive electrode sheet, the pressing temperature is 70° C. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0075] Comparative Example 2

[0076] This comparative example prepares a lithium battery with reference to Example 1. The difference between this comparative example and Example 1 is that in the process of compounding the composite separator and the positive electrode sheet, the pressing temperature is 45° C. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0077] Comparative Example 3

[0078] This comparative example prepares a lithium battery with reference to Example 1. The difference between this comparative example and Example 1 is that in the process of compounding the composite separator and the negative electrode sheet, the pressing temperature is 48° C. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0079] Comparative Example 4

[0080] This comparative example prepares a lithium battery with reference to Example 1. The difference between this comparative example and Example 1 is that in the process of compounding the composite separator and the negative electrode sheet, the pressing temperature is 20° C. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0081] Test Example 1

[0082] 1. Test object:

[0083] Examples 1 to 13 and comparative examples 1 to 4 were used as test objects of this test example.

[0084] 2. Test items:

[0085] (1) Adhesion test between composite diaphragm and positive electrode sheet: The tensile machine tests the peeling force between the composite diaphragm and the positive electrode sheet.

[0086] (2) Adhesion test between the composite diaphragm and the negative electrode sheet: The tensile machine tests the peeling force between the composite diaphragm and the negative electrode sheet.

[0087] (3) Battery high temperature cycle capacity retention rate: Under a 45°C test environment, the battery was charged and discharged by Xinwei equipment; it was charged to 3.65V at a constant current and constant voltage of 1C current, left to stand for 10 minutes, and then discharged to 2.5V at a constant current of 1C current. The final result is expressed as the capacity retention rate of 300 cycles of 1C / 1C cycle charge and discharge, and the calculation formula is as follows: Capacity retention rate (%) = discharge capacity per cycle / first discharge capacity × 100%.

[0088] 3. Test results:

[0089] Table 1 Performance test results of lithium batteries of Examples 1 to 13 and Comparative Examples 1 to 4

[0090]

[0091]

[0092] The test results are shown in Table 1. Comparing the performance test results corresponding to Example 1 with those of Comparative Example 1, it can be found that the bonding force between the composite diaphragm and the positive electrode sheet prepared in Comparative Example 1 is significantly lower than that in Example 1, and the high-temperature cycle capacity retention rate of the battery is significantly lower than that in Example 1. The reason is that under the same conditions of preparing other materials and operations of the battery, the pressing temperature T1 of Comparative Example 1 during the composite process of the positive electrode sheet and the composite diaphragm is higher than the Tg value (60°C) of the non-binder polymer C1, and the protrusion structure formed by the non-binder polymer C1 is prone to deformation, shedding and other undesirable problems, and it is difficult to maintain a good fit with the positive electrode sheet, thereby significantly deteriorating the bonding force between the composite diaphragm and the positive electrode sheet and the cycle characteristics of the battery. Comparing the performance test results corresponding to Example 1 with those of Comparative Example 2, it can be found that the bonding force between the composite diaphragm and the positive electrode sheet prepared in Comparative Example 2 is significantly lower than that in Example 1, and the high-temperature cycle capacity retention rate of the battery is significantly lower than that in Example 1. The reason is that, under the same conditions of other materials and operations for preparing the battery, the pressing temperature T1 of Comparative Example 2 during the composite process of the positive electrode sheet and the composite separator is lower than 50°C. This pressing temperature makes it difficult for the protrusion structure formed by the non-binder polymer C1 to fully fill the smaller pores on the surface of the positive electrode sheet, thereby significantly deteriorating the bonding strength between the composite separator and the positive electrode sheet and the cycle characteristics of the battery.

[0093] Comparing the performance test results corresponding to Example 1 and Comparative Example 3, it can be found that the bonding force between the composite separator and the negative electrode sheet prepared in Comparative Example 2 is significantly lower than that in Example 1, and the high-temperature cycle capacity retention rate of the battery is significantly lower than that in Example 1. The reason is that under the same conditions of other materials and operations for preparing the battery, the pressing temperature T2 of Comparative Example 3 during the composite process of the negative electrode sheet and the composite separator is higher than the Tg value (40°C) of the non-binder polymer C2, and the protrusion structure formed by the non-binder polymer C2 is prone to deformation, shedding and other undesirable problems, and it is difficult to maintain a good fit with the negative electrode sheet, thereby significantly deteriorating the bonding force between the composite separator and the negative electrode sheet and the cycle characteristics of the battery. Comparing the performance test results corresponding to Example 1 and Comparative Example 4, it can be found that the bonding force between the composite separator and the negative electrode sheet prepared in Comparative Example 4 is significantly lower than that in Example 1, and the high-temperature cycle capacity retention rate of the battery is significantly lower than that in Example 1. The reason is that, under the same conditions of other materials and operations for preparing the battery, the pressing temperature T2 of the negative electrode sheet and the composite separator in the composite process of Example 4 is lower than 28°C. This pressing temperature makes it difficult for the protrusion structure formed by the non-binder polymer C2 to fully fill the smaller pores on the surface of the negative electrode sheet, thereby significantly deteriorating the bonding strength between the composite separator and the negative electrode sheet and the cycle characteristics of the battery.

[0094] The performance test results of Example 1 are compared with those of Examples 2-3. As shown in Table 1, under the same conditions of other materials and operation for preparing the battery, the D 50 The ratio of the thickness of the first base coating layer to that of the first base coating layer is greater than 4:1. The D 50 The ratio of the thickness of the first base coating layer to the thickness of the first base coating layer is less than 1.3:1, and the bonding force between the composite separator and the positive electrode sheet obtained is lower than that of Example 1, and the high temperature cycle capacity retention rate of the battery is lower than that of Example 1. This shows that, compared with Examples 2 and 3, Example 1 further reasonably sets the D of the non-binder polymer C1. 50 The ratio of the thickness of the non-adhesive polymer C1 to the thickness of the first base coating is beneficial to ensure that the non-adhesive polymer C1 can be stably and firmly embedded in the first base coating of the composite diaphragm, thereby further helping the protruding structure formed by the non-adhesive polymer C1 to be stably and firmly embedded in the pores of the positive electrode sheet, thereby improving the bonding effect and fit between the composite diaphragm and the positive electrode sheet, and improving the cycle characteristics of the lithium battery.

[0095] The performance test results of Example 1 are compared with those of Examples 4-5. As shown in Table 1, under the same conditions of other materials and operation for preparing the battery, the D 50 The ratio of the thickness of the second base coating layer to the thickness of the second base coating layer is greater than 4:1. The D 50 The ratio of the thickness of the composite separator to the second base coating is less than 1.3:1, and the bonding force between the composite separator and the negative electrode sheet obtained is lower than that of Example 1, and the high temperature cycle capacity retention rate of the battery is lower than that of Example 1. This shows that, compared with Examples 4 and 5, Example 1 further reasonably sets the D of the non-binder polymer C2. 50 The ratio of the thickness of the non-adhesive polymer C2 to the thickness of the second base coating is beneficial to ensure that the non-adhesive polymer C2 can be stably and firmly embedded in the second base coating of the composite diaphragm, thereby further helping the protruding structure formed by the non-adhesive polymer C2 to be stably and firmly embedded in the pores of the negative electrode sheet, thereby improving the bonding effect and fit between the composite diaphragm and the negative electrode sheet, and improving the cycle characteristics of the lithium battery.

[0096] The performance test results of Example 1 and Example 6 are compared. As shown in Table 1, under the same conditions of other materials and operations for preparing the battery, the content of the non-binder polymer C1 in the first coating slurry used to form the porous active layer on the positive electrode side of the composite diaphragm in Example 6 is relatively small, and the bonding force between the composite diaphragm and the positive electrode sheet obtained is lower than that of Example 1, and the high-temperature cycle capacity retention rate of the battery is lower than that of Example 1. This shows that, relative to Example 6, Example 1 effectively regulates the content of the non-binder polymer C1 in the porous active layer on the positive electrode side, so that the surface of the composite diaphragm has a sufficient amount of protrusion structure, which effectively increases the probability of the non-binder polymer C1 being embedded in the first positive active coating of the positive electrode sheet, thereby improving the bonding effect and fit between the composite diaphragm and the positive electrode sheet; at the same time, the high Tg value non-binder polymer C1 of the above content can effectively ensure the thermal shrinkage performance and air permeability of the diaphragm, thereby further improving the cycle characteristics of the lithium battery.

[0097] The performance test results of Example 1 are compared with those of Examples 8 to 9. As shown in Table 1, under the same conditions of other materials and operations for preparing the battery, the content of non-binder polymer C2 in the second coating slurry used to form the porous active layer on the negative electrode side of the composite separator in Example 8 is relatively small, and the content of non-binder polymer C2 in the second coating slurry used to form the porous active layer on the negative electrode side of the composite separator in Example 9 is relatively large, so the bonding force between the composite separator and the negative electrode sheet obtained is lower than that of Example 1, and the high temperature cycle capacity retention rate of the battery is lower than that of Example 1. This shows that, compared with Examples 8 and 9, Example 1 effectively regulates the content of non-binder polymer C2 in the porous active layer on the negative electrode side, and the appropriate content of low Tg value non-binder polymer C2 can not only ensure the excellent thermal shrinkage performance of the composite separator, but also ensure that the surface of the composite separator has an appropriate amount of protrusion structure, so that the fit between the composite separator and the negative electrode sheet is maintained at a high level, thereby improving the bonding effect and fit between the composite separator and the negative electrode sheet, and making the cycle characteristics of the lithium battery better.

[0098] Comparing the performance test results corresponding to Example 1 with those of Example 10, it can be found that the bonding force between the composite diaphragm prepared in Example 10 and the positive electrode sheet is lower than that of Example 1, and the high temperature cycle capacity retention rate of the battery is lower than that of Example 1. The reason is that, under the same conditions of preparing other materials and operations of the battery, Example 10 uses a non-binder polymer C1 with a Tg value higher than 90°C. The elasticity of the non-binder polymer C1 is poor, and it is difficult to fully fill the smaller pores of the positive electrode sheet during the composite process of the positive electrode sheet and the composite diaphragm (pressing temperature T1 is 52°C), thereby reducing the bonding force between the composite diaphragm and the positive electrode sheet and the cycle characteristics of the battery. Comparing the performance test results corresponding to Example 1 with those of Example 11, it can be found that the bonding force between the composite diaphragm prepared in Example 11 and the negative electrode sheet is lower than that of Example 1, and the high temperature cycle capacity retention rate of the battery is lower than that of Example 1. The reason is that, under the same conditions of preparing other materials and operating conditions of the battery, Example 11 adopts a non-binder polymer C2 with a Tg value higher than 90°C. The elasticity of the non-binder polymer C2 is not enough to fully fill the pores of the negative electrode sheet during the composite process of the negative electrode sheet and the composite separator (pressing temperature T2 is 30°C), thereby reducing the bonding force between the composite separator and the negative electrode sheet and the cycle characteristics of the battery.

[0099] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A battery cell, characterized in that: It includes a positive electrode sheet, a composite separator and a negative electrode sheet arranged in sequence; The positive electrode sheet comprises a positive electrode current collector and a first positive electrode active coating, wherein the first positive electrode active coating is disposed on the surface of the positive electrode current collector facing the composite separator; the negative electrode sheet comprises a negative electrode current collector and a first negative electrode active coating, wherein the first negative electrode active coating is disposed on the surface of the negative electrode current collector facing the composite separator; The composite separator comprises a porous substrate layer, a positive electrode side porous active layer, and a negative electrode side porous active layer, wherein the surface of the porous substrate layer facing the positive electrode sheet is a first surface, and the positive electrode side porous active layer is arranged on the first surface, and the surface of the porous substrate layer facing the negative electrode sheet is a second surface, and the negative electrode side porous active layer is arranged on the second surface; The positive electrode side porous active layer includes a first base coating and a non-binder polymer C1 embedded in the first base coating, wherein the D 50 > the thickness of the first base coating; the porous active layer on the negative electrode side includes a second base coating and a non-binder polymer C2 embedded in the second base coating, and the D of the non-binder polymer C2 50 > the thickness of the second base coating; The compaction density of the first positive electrode active coating is 2.05-3.60 g / cm 3 ; The compaction density of the first negative electrode active coating is 1.40-1.85 g / cm 3 ; The composite of the positive electrode sheet and the composite separator is achieved by a pressing process I, the pressing temperature T1 of the pressing process I satisfies 50°C≤T1<Tg value of the non-binder polymer C1, and the pressing pressure of the pressing process I is not less than 0.2 tons; The composite of the negative electrode sheet and the composite separator is achieved through a pressing process II, the pressing temperature T2 of the pressing process II satisfies 28°C≤T2<Tg value of the non-binder polymer C2, and the pressing pressure of the pressing process II is not less than 0.2 tons.

2. The battery cell according to claim 1, characterized in that: The non-adhesive polymer C1 has 50 :The thickness of the first base coating layer = (1.3-4):

1.

3. The battery cell according to claim 1, characterized in that: The non-adhesive polymer C2 D 50 :The thickness of the second base coating layer=(1.3~4):

1.

4. The battery cell according to claim 1, characterized in that: The mass proportion of the non-binder polymer C1 in the porous active layer on the positive electrode side is 3% to 22%.

5. The battery cell according to claim 1, characterized in that: The mass proportion of the non-binder polymer C2 in the porous active layer on the negative electrode side is 2% to 17%.

6. The battery cell according to claim 1, characterized in that: The Tg value of the non-binder polymer C1 is 55-90°C.

7. The battery cell according to claim 1, characterized in that: The Tg value of the non-binder polymer C2 is 30 to 90°C.

8. The battery cell according to claim 1, characterized in that: The pressing temperature T1 of the pressing process I is 50 to 70° C., and the pressing pressure of the pressing process I is 0.2 to 14 tons; The pressing temperature T2 of the pressing process II is 28 to 48° C., and the pressing pressure of the pressing process II is 0.2 to 14 tons.

9. The battery cell according to any one of claims 1 to 8, characterized in that: The first positive electrode active coating layer includes a first positive electrode active material. 50 The first negative electrode active coating comprises a first negative electrode active material, and the D 50 5~20μm.

10. A lithium battery, characterized in that: Comprising the battery cell as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Pole piece and diaphragm compounding process and lithium battery core preparation process

    CN112670592A

  • Positive electrode active substance for nonaqueous electrolyte secondary cell and nonaqueous electrolyte secondary cell

    JP2001250552A